2022
DOI: 10.3168/jds.2022-22071
|View full text |Cite
|
Sign up to set email alerts
|

Impact of somatic cell count combined with differential somatic cell count on milk protein fractions in Holstein cattle

Abstract: Udder health in dairy herds is a very important issue given its implications for animal welfare and the production of high-quality milk. Somatic cell count (SCC) is the most widely used means of assessing udder health status. However, differential somatic cell count (DSCC) has recently been proposed as a new and more effective means of evaluating intramammary infection dynamics. Differential SCC represents the combined percentage of polymorphonuclear neutrophils and lymphocytes (PMN-LYM) in the total SCC, with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…27,48 In particular, Thomas et al 48 showed that, following artificial S. uberis infection, the proteome and peptidome of milk still change even when the infection is resolved, supporting the hypothesis that degradation is related more to the immune response than to the etiological agent. Some authors also found a considerable increase in acute phase proteins 48 after occurrence of mastitis, in addition to the decrease in caseins 34,54,55 and the increase in blood serum proteins. 56 In our study, we did not find any significant peptide derived by proteins such as α-lactalbumin, secretory IgA, or lactoferrin, in line with other studies.…”
Section: ■ Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…27,48 In particular, Thomas et al 48 showed that, following artificial S. uberis infection, the proteome and peptidome of milk still change even when the infection is resolved, supporting the hypothesis that degradation is related more to the immune response than to the etiological agent. Some authors also found a considerable increase in acute phase proteins 48 after occurrence of mastitis, in addition to the decrease in caseins 34,54,55 and the increase in blood serum proteins. 56 In our study, we did not find any significant peptide derived by proteins such as α-lactalbumin, secretory IgA, or lactoferrin, in line with other studies.…”
Section: ■ Discussionmentioning
confidence: 94%
“…Some authors also found a considerable increase in acute phase proteins 48 after occurrence of mastitis, in addition to the decrease in caseins 34 , 54 , 55 and the increase in blood serum proteins. 56 In our study, we did not find any significant peptide derived by proteins such as α-lactalbumin, secretory IgA, or lactoferrin, in line with other studies.…”
Section: Discussionmentioning
confidence: 95%
“…In healthy cows, the physiological norm of somatic cell content is between 100 and 170 thousand/cm 3 . Often, this number depends on the individual characteristics of the animal [ 42 , 43 ]. Additionally, we analyzed the results with a somatic cell count of more than 1,000 thousand cells/ml, which is evidence of the development of the inflammatory process in one or several quarters of the mammary glands.…”
Section: Resultsmentioning
confidence: 99%
“…Matei et al [62] reported a significantly higher concentration of total protein in milk from cows affected by mastitis compared to healthy ones. Thus, this increase in the concentration of total proteins in the milk of cows affected by mastitis could be a consequence of the high permeability of blood vessels and the release of serum proteins from the blood into the milk, as well as the migration of leukocytes [63]. However, Qayyum et al [51] found a lower concentration of total protein in milk from cows with mastitis compared to healthy ones.…”
Section: Discussionmentioning
confidence: 99%